Haemato- Biochemical and Electrolyte Changes in Naturally Occurring Theileria Associated Bovine Anaemia (Taba) - Yogeshpriya Somu; Saravanan Mani (Research Aspects in Agriculture and Veterinary Science Vol. 2, 2021)
The aim of this study was to ascertain the changes in haematology and serum electrolytes in the cows naturally infected with theileriosis. A total of 102 cross bred cows of age 2-5 years were screened and examined in the study. Among those, twelve were found naturally infected by theileria. Another twelve of the same age and apparently healthy animals were kept as control. Haematological values of haemoglobin, packed cell volume, total erythrocyte count, mean corpuscular volume and mean corpuscular haemoglobin concentration were significantly (p < 0.05) lower in anaemic cattle compared to non-anaemic (healthy) cattle. Comparisons of electrolyte balance in this study showed significant decrease at the level of p<0.05 in sodium and ionized calcium concentrations of anaemic animals when compared to the control group. However, differences in blood potassium and total calcium levels were not significant (p>0.05). Comparisons of biochemical values indicated a significant increase (p < 0.05) in blood urea nitrogen (BUN) and creatinine level, while decrease (p < 0.05) in total protein and albumin concentration in anaemic animals as compared to control group. These results indicated an overall poor picture of circulating blood in animals suffering from theileria associated bovine anaemia.